Tailoring porosity and antibacterial activity in MgO/ZrO2-modified kaolin ceramics for use in wastewater filtration systems - Dikra Bouras; Mamoun Fellah; Billel Salhi; Nestor Ankah; Neçar Merah (Journal of Science: Advanced Materials and Devices)
The advancement of natural ceramic materials with multifunctional properties is essential for promoting sustainable solutions in wastewater treatment and microbial control. This study examines kaolinite-based ceramics from Algerian DjebelDebbagh clay (DD2) modified with magnesium oxide (MgO) at concentrations of 0, 40, and 80 wt%, both with and without the addition of 38 wt% zirconium dioxide (ZrO2) (DD2Z), to evaluate their structural, adsorptive, and antibacterial properties. Ceramic composites were synthesized through high-temperature sintering and characterized using X-ray diffraction (XRD), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM/EDS), Brunauer-Emmett-Teller (BET) surface area analysis, thermogravimetric analysis (TGA) and atomic force microscopy analysis (AFM). Phase analysis indicated the development of mullite, spinel, zircon, and magnesium silicate phases, which progressed with higher MgO content. The incorporation of ZrO2 enhanced mesoporosity and surface area, whereas MgO improved permeability and facilitated bacterial inactivation. The antibacterial activity against Pseudomonas putida was assessed through immersion and agar diffusion methods, revealing that the DD2Z + 80 wt% MgO sample demonstrated the highest inhibition rate of 75 % and the largest inhibition zone measuring 12.5 mm. Liquid diffusion tests confirmed enhanced wettability and pore connectivity in the ZrO2-MgO systems. The findings indicate that MgO- and ZrO2-modified natural kaolinite ceramics may serve as cost-effective, durable, and antibacterial materials suitable for integrated wastewater treatment applications.